Cultures of curriculum - Joseph, Pamela Bolotin (New York Routledge, 2011)
"Using "cultures of curriculum" as a lens, this clear, compelling text reveals and critically examines the belief systems and classroom practices of curricular orientations in contemporary American society. It is designed to foster awareness, examination, and deliberation about the curricula planned for and carried out in classrooms and schools; to inspire conversations about theory and practice as well as political, social, and moral issues; and to expand critical consciousness about approaches to curriculum and practice. Readers are encouraged to give serious attention to the issues this book raises for them, and to join with their colleagues, students, and communities in considering how to create curricula with purpose and congruent practices and to reculture classrooms and schools. A framework of inquiry is presented to facilitate such reflection and to accomplish these goals."--Publisher's description.
Conceptualizing curriculum / Pamela Bolotin Joseph -- Understanding curriculum as culture / Pamela Bolotin Joseph -- Narrowing the curriculum / Pamela Bolotin Joseph, Nancy Stewart Green, Edward R. Mikel, and Mark A. Windschitl -- Reculturing the curriculum / Pamela Bolotin Joseph, Edward R. Mikel, and Mark A. Windschitl -- Constructing understanding / Mark A. Windschitl -- Developing self and spirit / Stephanie Luster Bravmann Educating through occupations / Nancy Stewart Green and Pamela Bolotin Joseph -- Connecting to the canon / Pamela Bolotin Joseph -- Sustaining indigenous traditions / Tarajean Yazzie-Mintz -- Deliberating democracy / Edward R. Mikel -- Confronting the dominant order / Mark A. Windschitl and Pamela Bolotin Joseph -- Envisioning peace / Pamela Bolotin Joseph.
Keywords: Curriculum planning -- United States; Education -- Curricula -- Social aspects -- United States